2009
DOI: 10.1021/es8032296
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Relevant Properties of Diesel Particulate Emissions: Results from a Piggyback Study in Bangkok, Thailand

Abstract: A "piggyback" approach is used to characterize aerosol emissions to obtain input for large-scale models of atmospheric transport. Particulate and gaseous emissions from diesel trucks, light-duty vehicles, and buses were measured by the Bangkok Pollution Control Department as part of the Developing Integrated Emissions Strategies for Existing Land Transport (DIESEL) project. We added filter-based measurements of carbonaceous composition, particulate light absorption, and water uptake. For 88 "normal" diesel veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 90 publications
(127 reference statements)
1
22
0
Order By: Relevance
“…2.3. The scaling factor was derived from Klimont et al (2017), who provided the global values for diesel and gasoline vehicles across different emission standard vehicles, and also based on PM emission factors measured in developing countries (Subramanian et al, 2009). On average, light duty diesel vehicles are scaled by a factor of 5 to get a value of 8.1 g kg −1 , and on average heavyduty diesel vehicles are scaled by a factor of 2 to get a value of 13.3 g kg −1 for superemitter vehicles.…”
Section: Emission Trends and Sectoral Contribution To National Estimatesmentioning
confidence: 99%
“…2.3. The scaling factor was derived from Klimont et al (2017), who provided the global values for diesel and gasoline vehicles across different emission standard vehicles, and also based on PM emission factors measured in developing countries (Subramanian et al, 2009). On average, light duty diesel vehicles are scaled by a factor of 5 to get a value of 8.1 g kg −1 , and on average heavyduty diesel vehicles are scaled by a factor of 2 to get a value of 13.3 g kg −1 for superemitter vehicles.…”
Section: Emission Trends and Sectoral Contribution To National Estimatesmentioning
confidence: 99%
“…This database improves the resolution of the spatial distribution of emissions for large countries (12). To fill the data gap in developing countries, a set of EF BC values has been compiled for various residential solid fuel combustion devices and vehicles (13)(14)(15)(16)(17)(18)(19)(20). In addition to the problems with the emission inventories, the coarse resolution of existing global aerosol models also hinders our ability to capture detailed spatial variation, leading to poor agreement between model prediction and observations (7).…”
mentioning
confidence: 99%
“…Unregulated HDDV trucks and buses, which may have been built to similar specifications, were measured by Subramanian et al (2009) in Thailand, with a reported average PM EF of 4-10 g/kg. Several studies also measured smoke opacity from these vehicles to be around 20% (Springer et al, 1974;Stahman et al, 1968;Williams et al, 1989) which can be converted to a PM EF of 5-7 g/kg as described in the supporting information Text S5.…”
Section: Heavy-duty and Light-duty Vehiclesmentioning
confidence: 99%